Capsule Endoscopy as a Diagnostic Tool for Inflammatory Bowel Disease in a Patient with Multiple Myeloma - Rizkiawan, Naufali; Mahmudah, Isna; Miftahussurur, Muhammad (The Indonesian Society for Digestive Endoscopy, 2025)
Capsule endoscopy is an important tool for minimally invasive evaluation of the small bowel, allowing improved diagnostic yield with low complication rates relative to traditional modalities. Here, we present the first case of inflammatory bowel disease (IBD) diagnosed by a capsule endoscopy in Surabaya. There was a case of a patient who suffered chronic diarrhea for four months. When the patient experienced persistent diarrhea, generalized weakness was then reported as a symptom. The patient then received a conventional endoscopy and was planned for a colonoscopy. However, the endoscopy was canceled due to the patient's respiratory distress. The patient underwent capsule endoscopy, where hyperemia and erosion from the small intestine to the colon were found. The diagnosis of IBD was established and the patient was given sulfasalazine 500 mg every 24 hours. In order to image the small intestine endoscopically, capsule endoscopy remains to be the preferred method. This case serves as an example of the advantages of capsule endoscopy, especially in terms of the diagnosis of inflammatory bowel disease.